How Healthcare Infrastructure Contributes to The Sustainability of Future African Mega-Cities - Lekalakala, Kgaugelo; Nkala, Khulani; Ndirangu, Maureen; Makofane, Tumelo; Musanda, Chilando; Mavuti, Chris (MAJ - Malaysia Architectural Journal, 2025)
Worldwide there has been rapid rural-urban migration in search of better economic opportunities. In developing countries, this movement has created an imbalance in the provision of services putting a lot of pressure on existing infrastructure and resources. Further, in these cities there is a lack of sustainable solutions to the challenges associated with large population densities. Among other services, healthcare and its associated infrastructure are critical in creating sustainable urban environments. Separate spatial planning practices, differences in social service provision among ethnic groups and disparities in economic conditions, among others, are all factors that illustrate the inequities experienced not only in the health sector but in other societal structures. This ignited locals to migrate to urban areas or towns looking for jobs and better social services. With high urbanization, public healthcare infrastructure development has been overstretched leading to overcrowding and heavy deterioration. According to UN-Habitat, it is estimated that, for South Africa, the urban population will be at 71% by 2030 and 80% by 2050 indicating an increased burden on the healthcare infrastructure. With this high rate of urbanization in the post-apartheid era, it has become crucial to look at alternative ways of redistributing the resources, i.e., supporting smaller towns such as Giyani, in Limpopo region where densification and organic economic growth is happening. This research examines healthcare infrastructure built during the apartheid period. It highlights disparities in quality, access, and planning, that persists as remnants of the apartheid planning policies. Findings indicated that healthcare infrastructure can be master planned to support positive economic transformation which will in turn be more attractive to healthcare workforce, who will be more willing to relocate to growing cities. And with hospitals being employers of large numbers of people, this can be a catalyst to support the growing cities to develop further sustainably.